The Relationship Between Childhood Trauma and Personality Traits with Attitudes Toward Childbearing in Married Women Aged 25–45 - Dastani Hossein Abadi , Hakime; Shirinzadeh, Samad; Poursalehy , Marzieh; Mollazadeh , Alireza (Psychology of Woman Journal, 2026)
Objective: The present study aimed to examine the relationship between childhood trauma and personality traits with attitudes toward childbearing in married women aged 25–45.Methods and Materials: This study employed a fundamental, descriptive–correlational design. The statistical population consisted of married women aged 25–45 who referred to psychological clinics and mental health centers in districts 1 to 5 of Tehran. A sample of 222 participants was selected using a convenience sampling method, based on recommended sample sizes for correlational research and considering potential attrition. Data were collected using the Attitudes Toward Fertility and Childbearing Scale (AFCS), the Childhood Trauma Questionnaire (CTQ), and the short form of the Five-Factor Personality Inventory (NEO-FFI). Data analysis was conducted using SPSS version 27 at both descriptive and inferential levels, including Pearson correlation coefficients and simultaneous multiple regression analysis to examine relationships and predictive power among variables.Findings: The results indicated that emotional abuse (r = -0.19, p < 0.01) and emotional neglect (r = -0.16, p < 0.05) were significantly and negatively correlated with attitudes toward childbearing, whereas other trauma dimensions showed non-significant relationships. Among personality traits, extraversion (r = 0.26, p < 0.01), openness to experience (r = 0.17, p < 0.01), and agreeableness (r = 0.22, p < 0.01) demonstrated significant positive correlations with attitudes toward childbearing. The results of multiple regression analysis revealed that extraversion (β = 0.15, p = 0.046) and openness to experience (β = 0.13, p = 0.040) significantly predicted attitudes toward childbearing, while childhood trauma variables did not show significant predictive effects in the presence of personality traits. The overall regression model was statistically significant (F = 5.49, p < 0.01) and explained 11% of the variance in attitudes toward childbearing.